2012
DOI: 10.1186/1471-230x-12-118
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and apoptosis-related genes in chronic liver disease and hepatocellular carcinoma

Abstract: BackgroundDysregulation of autophagy is important in the pathogenesis of many diseases, including cancer. Several aspects of the biological role of autophagy are however still unclear and the relationship between apoptosis and autophagy, particularly in the liver has yet to be thoroughly explored. In this study we evaluated the expression of Beclin 1 (one of the main autophagocytic agents, which bridges autophagy, apoptosis and both differentiation), and both pro- (Bad, Bax) and anti-apoptotic (Bcl-2, Bcl-xL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 42 publications
3
32
0
1
Order By: Relevance
“…For instance, a high incidence of spontaneous HCC is observed in mice in which homozygous Beclin-1 is knocked out and Atg5 or Atg7 is deleted [20; 21]. In addition, Beclin-1 expression is decreased in human HCC tissues and is positively associated with longer time to recurrence and longer overall survival [22]. Similarly, the downregulation of LC3 expression is detected in HCC, and LC3 expression is correlated with a longer overall survival of HCC patients, particularly those in advanced stages, suggesting that LC3 is an independent predictor of prognosis in patients with HCC [23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a high incidence of spontaneous HCC is observed in mice in which homozygous Beclin-1 is knocked out and Atg5 or Atg7 is deleted [20; 21]. In addition, Beclin-1 expression is decreased in human HCC tissues and is positively associated with longer time to recurrence and longer overall survival [22]. Similarly, the downregulation of LC3 expression is detected in HCC, and LC3 expression is correlated with a longer overall survival of HCC patients, particularly those in advanced stages, suggesting that LC3 is an independent predictor of prognosis in patients with HCC [23].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular autophagy, which is maintained during chronic liver injury, may play an important role in the sustainment of chronic liver disease and cancer development (Rautou et al, 2010; Kotsafti et al, 2012; Raitou et al, 2011). In this regard, there is evidence to suggest that mice with deletion of autophagy related genes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further studies are needed to clarify the role of autophagy in the process of liver fibrosis before a therapeutic approach targeting autophagy can be used. Previous studies showed that the mRNA levels of Beclin 1 were lower in HCC tissues than in chronic hepatitis or cirrhosis [86,87]. In addition, other in vivo and in vitro studies supported that the autophagic pathway was inhibited in HCC [71,72,[88][89][90].…”
Section: Discussionmentioning
confidence: 57%